Cellular immune responses and immune escape mechanisms in breast cancer: determinants of immunotherapy - Domschke, Christoph; Schneeweiss, Andreas; Stefanovic, Stefan; Wallwiener, Markus; Heil, Jörg; Rom, Joachim; Sohn, Christof; Beckhove, Philipp; Schütz, Florian (Breast care, 2016)
More recently, immunotherapy has emerged as a novel potentially effective therapeutic option also for solid malignancies such as breast cancer (BC). Relevant approaches, however, are determined by the 2 main elements of cancer immunoediting - the elimination of nascent transformed cells by immunosurveillance on the one hand and tumor immune escape on the other hand. Correspondingly, we here review the role of the various cellular immune players within the host-protective system and dissect the mechanisms of immune evasion leading to tumor progression. If the immune balance of disseminated BC cell dormancy (equilibrium phase) is lost, distant metastatic relapse may occur. The relevant cellular antitumor responses and translational immunotherapeutic options will also be discussed in terms of clinical benefit and future directions in BC management.